Impacts on in‐event, ambulance and emergency department services from patients presenting from a mass gathering event: A retrospective analysis. (8th November 2018) - Ranse, Jamie; Lenson, Shane; Keene, Toby; Luther, Matt; Burke, Brandon; Hutton, Alison; Johnston, Amy NB; Crilly, Julia
Abstract: Objective: The aim of this study was to describe the in‐event, ambulance and ED impacts of patient presentations from an Australian mass gathering event (MGE) including patient demographics, provision of care, length of stay and discharge disposition. Methods: This research was set at one MGE in Australia. The MGE had one first aid post and one in‐event health team staffed by doctors, nurses and paramedics. A retrospective analysis of patient care records from providers of in‐event, ambulance and ED services was undertaken. Data analysis included descriptive and inferential statistics. Results: Of the 20 000 MGE participants, 197 (0.99% [95% CI 0.86–1.13], 9.85/1000) presented for in‐event first aid care, with 24/197 (12.2% [95% CI 8.33–17.49], 1.2/1000) referred to in‐event health professionals. Fifteen of the referred patients (62.5% [95% CI 42.71–78.84]) returned to the MGE following administration of intravenous fluids ( n = 13) and/or anti‐emetics ( n = 11). Seven (29.2% [95% CI 14.92–49.17], 0.35/1000) were referred to ambulance paramedic care, requiring endotracheal intubation ( n = 1) and airway adjuncts ( n = 3) prior to transportation to ED; these patients had an ED median length of stay of 7 h (5.5–12.5) receiving imaging and ventilator support. Five were discharged from ED, one required an operation and another required intensive care unit admission. Conclusions: There was an impact on in‐event, ambulance and ED services from this MGE but the in‐event model of care may have limited ambulance usage and ED visits. The ED length of stay was greater than the national median, perhaps reflecting the appropriateness of transport and nature of care requirements while in the ED.